Co-Delivery of Imiquimod and Curcumin by Nanoemugel for Improved Topical Delivery and Reduced Psoriasis-Like Skin Lesions - Mohammed S. Algahtani; Mohammad Zaki Ahmad; Ihab Hamed Nourein; Javed Ahmad (Biomolecules, 2020)
The current investigation aimed to improve the topical efficacy of imiquimod in combination with curcumin using the nanoemulsion-based delivery system through a combinatorial approach. Co-delivery of curcumin acts as an adjuvant therapeutic and to minimize the adverse skin reactions that are frequently associated with the topical therapy of imiquimod for the treatment of cutaneous infections and basal cell carcinomas. The low-energy emulsification method was used for the nano-encapsulation of imiquimod and curcumin in the nanodroplet oil phase, which was stabilized using Tween 20 in an aqueous dispersion system. The weak base property of imiquimod helped to increase its solubility in oleic acid compared with ethyl oleate, which indicates that fatty acids should be preferred as the oil phase for the design of imiquimod-loaded topical nanoemulsion compared with fatty acid esters. The phase diagram method was used to optimize the percentage composition of the nanoemulsion formulation. The mean droplet size of the optimized nanoemulsion was 76.93 nm, with a polydispersity index (PdI) value of 0.121 and zeta potential value of −20.5 mV. The optimized imiquimod-loaded nanoemulsion was uniformly dispersed in carbopol 934 hydrogel to develop into a nanoemulgel delivery system. The imiquimod nanoemulgel exhibited significant improvement (p < 0.05) in skin permeability and deposition profile after topical application. The in vivo effectiveness of the combination of imiquimod and curcumin nanoemulgel was compared to the imiquimod nanoemulgel and imiquimod gel formulation through topical application for ten days in BALB/c mice. The combination of curcumin with imiquimod in the nanoemulgel system prevented the appearance of psoriasis-like symptoms compared with the imiquimod nanoemulgel and imiquimod gel formulation entirely. Further, the imiquimod nanoemulgel as a mono-preparation slowed and reduced the psoriasis-like skin reaction when compared with the conventional imiquimod gel, and that was contributed to by the control release property of the nano-encapsulation approach.